Electricricity Generation from Municipal Solid Wastes (MSW) in Kano Metropolis, through Different Waste to Energy Conversion Processes: A Comparative Study - T., Baba M.; A., Adamu A.; A., Yola I. (Darul Yasin Al Sys, 2025)
The study intends to carry out a Comparative study of different Waste to Energy (WTE) conversion processes (Incineration, Anaerobic Digestion, and Landfill Gas to Energy) in terms of Electricity Generation from Municipal Solid Wastes (MSW) in Kano Metropolis, Nigeria in order to determine the most favourable process among them. The amount of landfill gas from the landfills sites (dumpsites) in Kano metropolis was estimated using Landfill Gas Emission Model (LandGEM) 3.02 software. The American Society for Testing and Materials (ASTM) methods (ASTM D5231) and (ASTM D2382-88), per capita waste generation and the population data obtained from national population commission (NPC), LandGEM 3.02 software, laboratory bomb calorimeter (Model 6100, Bomb Calorimeter, Parr Instrument Co., Moline, Illinois), were used as materials for the study. The results revealed that the amount of waste that could be used for landfill gas to energy Incineration, and Anaerobic Digestion were estimated as 9.004,560.61 tons/yr, 4,556,887.64 tons/yr and 4,447,672.97 tons/yr respectively. It was also known that, based on the amount of electricity that can be generated, the LFGTE presents the appropriate option of WTE process for Kano metropolis, Nigeria with electricity generation of 33,175,973.48KWh/yr. It is recommended that further study be carried out on the economic feasibility of the two processes.